2023
DOI: 10.31674/ijmhs.2023.v07i01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Social Media to Attract Customers for Start-up Business

Abstract: Marketing professionals are paying more and more attention to social media because it is among the most effective methods for communicating with customers about businesses. Despite its expanding significance, little investigation has looked at how social media marketing strategies affect consumers' awareness of the brand. In this study, a conceptual framework is proposed for analysing how social media marketing characteristics affect customer loyalty and perception across businesses with various levels of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…According to the "2022 Qiangua Active User Portrait Trend Report (Red Platform)", Red has over 200 million monthly active users, 72% of whom are post-90s [9]. Lui Hilong suggested that companies can choose the most successful social media platforms to draw in their target clients by determining which social media platforms are appropriate for various user traits and product categories [10]. Therefore, comparing the age characteristics of users on the two platforms of TikTok and Red, it can be concluded that the reason why Lancôme decided to focus its advertising on Red and TikTok is that it found the fact that the users of the two platforms are mainly young people, which coincides with the fact that Lancôme's advanced night cream target customers are young people.…”
Section: Choose the Right Channelsmentioning
confidence: 99%
“…According to the "2022 Qiangua Active User Portrait Trend Report (Red Platform)", Red has over 200 million monthly active users, 72% of whom are post-90s [9]. Lui Hilong suggested that companies can choose the most successful social media platforms to draw in their target clients by determining which social media platforms are appropriate for various user traits and product categories [10]. Therefore, comparing the age characteristics of users on the two platforms of TikTok and Red, it can be concluded that the reason why Lancôme decided to focus its advertising on Red and TikTok is that it found the fact that the users of the two platforms are mainly young people, which coincides with the fact that Lancôme's advanced night cream target customers are young people.…”
Section: Choose the Right Channelsmentioning
confidence: 99%
“…By utilising social networking sites, technologies, internet analytics, and search engine marketing, particularly in cross-border transactions, business-to-business (B2B) selling has been redesigned (Barratt & Rosdahl, 2002). A social media plan is essential for considering both the effectiveness assessment method and all platform-specific factors, which has several advantages for a business (Hilong, 2023). With direct internet access to massive amounts of data and a thorough grasp of customer preferences, salespeople may now more successfully focus on the most lucrative aspects of managing client connections and global business possibilities.…”
Section: Introductionmentioning
confidence: 99%